Peran pelatihan strategi "Smart" dalam meningkatkan self-regulated learning (SRL) pada siswa SMP - Lidiawati, Krishervina Rani (Jurnal Psikologi Ulayat: Indonesian Journal of Indigenous Psychology, 2016)
This study examined the role of ‘SMART’ strategy in enhancing the Self- Regulation Learning (SRL) of Junior High School (SMP) students whose scores were under the school’s passing grade (KKM). Self-regulated learning (SRL) is a process in which a learner activates his thought (cognition), feeling (affection), and behavior and which is expected to help students achieve learning objectives systematically (Zimmerman & Schunk, 2001). SMART (Specific, Measureable, Attention, Realistic, and Time) is a strategy in a SRL process. There were 10 students who participated in this study; 6 males and 4 females. This study used quantitative action research which consisted of two cycles in each of which theresearcher measured and evaluated the findings. Using the different paired sample t-test, the result of the first cycle showed that there was no significant change in the participants’ self-regulation (t = 1.476, p > .05). In the second cycle, it was also shown that there was no significant change of SRL score in post-test 1 and post-test 2 (t = 0.152, p > .05).